Seismic Response of Reinforced Concrete Structures Using Pushover Analysis with Varying Number of Storeys - Muhammad Ariyanto; Ronny Hasudungan Purba; Hery Riyanto (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2026)
This study evaluates the influence of vertical geometric variation on the seismic response and inter-story drift of reinforced concrete Special Moment Resisting Frame (SMRF) buildings located in the high seismic zone of Bandar Lampung. Three hypothetical 30-meter-tall models were analyzed: Model A (12 stories), Model B (10 stories), and Model C (8 stories). Nonlinear static pushover analysis was performed in accordance with SNI 1726:2019 and ATC-40 criteria. The results indicate that variations in story height significantly affect the dynamic characteristics and deformation patterns of the structures. Model A exhibits the shortest natural period (T = 1.559 s) and the largest base shear capacity (8,722 kN), but shows more limited post-yield behavior due to the short column effect. Model C produces the highest drift ratio (1.072%) as a result of the more dominant P-Delta effect. All models achieve the Life Safety (LS) performance level, with the majority of plastic hinges remaining in the Immediate Occupancy (IO) category, indicating available deformation capacity. Within the scope of this study, Model B is considered the most balanced configuration in terms of stiffness, drift, and ductility, and is therefore recommended as a balanced vertical geometric configuration for 30-meter-high buildings.